Unrestrained Gαi2 Signaling Disrupts Neutrophil Trafficking, Aging, and Clearance - Yan, Serena Li-Sue; Hwang, Il-Young; Kamenyeva, Olena; Kabat, Juraj; Kim, Ji Sung; Park, Chung; Kehrl, John H. (Frontiers in Immunology, 2021)
Neutrophil trafficking, homeostatic and pathogen elicited, depends upon chemoattractant receptors triggering heterotrimeric G-protein Galpha/beta/gamma signaling, whose magnitude and kinetics are governed by RGS protein/Galphai interactions. RGS proteins typically limit Galphai signaling by reducing the duration that Galphai subunits remain GTP bound and able to activate downstream effectors. Yet how in totality RGS proteins shape neutrophil chemoattractant receptor activated responses remains unclear. Here, we show that C57Bl/6 mouse neutrophils containing a genomic knock-in of a mutation that disables all RGS protein-Galphai2 interactions (G184S) cannot properly balance chemoattractant receptor signaling, nor appropriately respond to inflammatory insults. Mutant neutrophils accumulate in mouse bone marrow, spleen, lung, and liver; despite neutropenia and an intrinsic inability to properly mobilize from the bone marrow. In vitro they rapidly adhere to ICAM-1 coated plates, but in vivo they poorly adhere to blood vessel endothelium. Those few neutrophils that cross blood vessels and enter tissues migrate haphazardly. Following Concanavalin-A administration fragmented G184S neutrophils accumulate in liver sinusoids leading to thrombo-inflammation and perivasculitis. Thus, neutrophil Galphai2/RGS protein interactions both limit and facilitate Galphai2 signaling thereby promoting normal neutrophil trafficking, aging, and clearance.